2002
DOI: 10.1073/pnas.052559499
|View full text |Cite
|
Sign up to set email alerts
|

Members of the PIAS family act as SUMO ligases for c-Jun and p53 and repress p53 activity

Abstract: The activity of the p53 tumor suppressor protein and the c-Jun protooncogene is regulated by posttranslational modifications, such as phosphorylation or ubiquitination. In addition, covalent attachment of the ubiquitin-like modifier SUMO appears to modulate their transcriptional activity. Sumoylation proceeds via an enzymatic pathway that is mechanistically analogous to ubiquitination, but requires a different E1-activating enzyme and Ubc9, a SUMO-specific E2-conjugating enzyme. Here, we show that two members … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
334
1
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 418 publications
(357 citation statements)
references
References 31 publications
20
334
1
2
Order By: Relevance
“…In this regard, the K ϩ channelassociated protein KChAP (35) has been shown to be a member of the PIAS family of proteins originally identified as negative regulators of several transcriptional responses (33). PIAS proteins possess intrinsic SUMO-specific E3 activity (48), and most of their transcriptional effects depend on this function. Although the regulatory consequences of KChAP association with Kv1.5 remain to be determined, the effects on surface expression observed for other Kv channels occur in a transcriptionindependent manner (33).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, the K ϩ channelassociated protein KChAP (35) has been shown to be a member of the PIAS family of proteins originally identified as negative regulators of several transcriptional responses (33). PIAS proteins possess intrinsic SUMO-specific E3 activity (48), and most of their transcriptional effects depend on this function. Although the regulatory consequences of KChAP association with Kv1.5 remain to be determined, the effects on surface expression observed for other Kv channels occur in a transcriptionindependent manner (33).…”
Section: Discussionmentioning
confidence: 99%
“…135 Several groups reported that p53 is a target protein for SUMO-1. 42,43,143,144 SUMO-1 is covalently attached to specific lysine residues of its target proteins by an enzymatic machinery, which is similar to that of ubiquitin modification. 45 p53 is SUMOlated at Lys386 within its regulatory domain through a complex containing the SUMO-1 conjugating enzyme Ubc9 and the SUMO-1 ligase protein inhibitor of activated STAT (PIAS)1.…”
Section: Regulation Of P53 Activity In Pml-nbsmentioning
confidence: 99%
“…45 p53 is SUMOlated at Lys386 within its regulatory domain through a complex containing the SUMO-1 conjugating enzyme Ubc9 and the SUMO-1 ligase protein inhibitor of activated STAT (PIAS)1. 51,144 However, addressing the function of p53 SUMOlation on p53 activity led to contradictory results, reaching from increased activity, 42,43 no effect 143 to decreased transcriptional activity of p53. 144 The reason for these discrepancies should be clarified in the future, although it is currently not clear whether SUMOlation of p53 might take place in PML-NBs.…”
Section: Regulation Of P53 Activity In Pml-nbsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conjugation requires an E1-activating enzyme and the E2 conjugase Ubc9. Ubc9 has a role in substrate recognition by binding a CKxE/D sequence often present in target proteins (Sampson et al, 2001), and SUMO conjugation may involve E3 ligases (Schmidt and Muller, 2002). SUMOylation has an important role in regulating transcription, protein trafficking, innate immunity and cell proliferation (Kerscher et al, 2006).…”
Section: Introductionmentioning
confidence: 99%